Association Between Violent Discipline at Home and Risk of Illness and Injury in Children: Findings From a Cross-sectional Study in Rural Western China - Huang, Yue (Journal of interpersonal violence, 2022)
To estimate the prevalence of violent discipline at home against young children, and to explore the potential association between violent discipline at home and multifaceted health risks in children. A community-based cross-sectional survey was conducted in twenty rural counties of weight provinces in western China. The information about child neglect and socio-demographic factors, exposure to different forms of violent discipline at home and four health outcomes was collected by face-to-face interview. Before analysis, the included interviews were weighted by the double-weighted comprehensive weighting. The proportion of children reported by primary caregivers to have experienced different forms of violent discipline by gender were calculated. To adjust the clustering effect of the survey design, two-level univariate and multivariate logistic regression models were constructed to evaluate the potential association between a child?s exposure to violent discipline at home and risk of suffering from diarrhea, fever, cough and injury. A total of 3,682 weighted interviews were finally included in the analysis. The prevalence of any violent discipline, psychological aggression, any physical punishment and severe physical punishment were 76.4%, 57.5%, 68.3% and 14.1%, respectively. In multivariate analysis, after adjusting for clustering, there was still a positive association between a child?s exposure to psychological aggression and risk of diarrhea (adjusted OR: 1.47, 95%CI: 1.14-1.90) and injury (adjusted OR: 1.95, 95%CI: 1.36-2.80); a child?s exposure to any physical punishment and risk of diarrhea (adjusted OR: 1.36, 95%CI: 1.04-1.77), cough (adjusted OR: 1.37, 95%CI: 1.14-1.66), and injury (adjusted OR: 2.05, 95%CI: 1.37-3.06); and a child?s exposure to severe physical punishment and risk of injury (adjusted OR: 2.07, 95%CI: 1.41-3.05). Considering that using violent discipline at home is prevalent in rural western China, and it could threaten young children?s health, effective measures to prevent young children from violent discipline are urgently needed.